Fenomena Minat Guru Gen Z Menjadi Supervisor Sebagai Dasar Foresight Dalam Perancangan Model Pembinaan Sosial - Raihanah; Arief Dermawan (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of education in the digital era demands innovation in supervisory practices and social coaching for teachers. In this context, a new phenomenon has emerged, namely the low interest of Generation Z teachers (aged 22–28) in taking on supervisory roles. Therefore, this study aims to map the support, barriers, perceptions, and foresight of Generation Z in designing future social coaching models, while linking them to social coaching theories and the characteristics of the modern generation.This research employs a descriptive qualitative method with a phenomenological design to explore the experiences, perceptions, and expectations of Gen Z teachers regarding supervision. A total of 12 informants aged 21–28 were selected using purposive sampling. Data were collected through observation, in-depth interviews, documentation, and triangulation. The analysis was carried out thematically using social coaching theory and Generation Z characteristics theory. The findings indicate that the main barriers for Gen Z teachers in becoming supervisors include non-transparent bureaucracy, lack of resources, psychological challenges such as low self-confidence, and generational gaps in leadership. Supporting factors include structural support from schools, mentoring programs, leadership training, opportunities to take on managerial tasks, and a collaborative school culture. Regarding preferred supervisory models, most respondents favored collaborative supervision, followed by artistic, clinical, and scientific models, with a strong inclination toward supervision that is dialogic, flexible, evidence-based, and humanistic. Through foresight, respondents predicted that future social coaching models should be adaptive, digital, data-driven, collaborative, holistic, and able to facilitate teachers’ creativity and interests. Keywords: Generation Z, educational supervision, social coaching, foresight, supervision model, digital era. Abstrak Perkembangan pendidikan di era digital menuntut adanya inovasi dalam praktik supervisi dan pembinaan sosial bagi guru. Pada konteks ini muncul fenomena baru, yaitu rendahnya minat guru Generasi Z (usia 22–28 tahun). Maka dari itu, Penelitian ini bertujuan memetakan dukungan, hambatan, persepsi, serta foresight Generasi Z dalam merancang model pembinaan sosial masa depan, sekaligus mengaitkannya dengan teori pembinaan sosial serta karakteristik generasi modern. Penelitian menggunakan metode kualitatif deskriptif dengan desain fenomenologi untuk menggali pengalaman, persepsi, dan harapan guru Gen Z terhadap supervisi. Sebanyak 12 informan berusia 21–28 tahun dipilih melalui teknik purposive sampling. Data dikumpulkan melalui observasi, wawancara mendalam, dokumentasi, serta triangulasi. Analisis dilakukan secara tematik dengan pendekatan teori pembinaan sosial dan teori karakteristik generasi Z.Hasil penelitian menunjukkan bahwa hambatan utama guru Gen Z menjadi supervisor meliputi birokrasi yang tidak transparan, kekurangan sumber daya, tantangan psikologis seperti kurang percaya diri, serta kesenjangan generasi dalam kepemimpinan. Adapun faktor pendukung meliputi dukungan struktural sekolah, program mentoring, pelatihan kepemimpinan, kesempatan memegang tugas manajerial, serta budaya sekolah yang kolaboratif. Dalam hal preferensi model supervisi, mayoritas responden memilih supervisi kolaboratif, disusul model artistik, klinis, dan ilmiah, dengan kecenderungan kuat pada supervisi yang dialogis, fleksibel, berbasis bukti, dan humanis. Melalui foresight, responden memprediksi bahwa model pembinaan sosial masa depan harus adaptif, digital, berbasis data, kolaboratif, holistik, dan memfasilitasi kreativitas serta minat guru. Kata kunci: Generasi Z, supervisi pendidikan, pembinaan sosial, foresight, model supervisi, era digital.